Hubungan Kepatuhan Minum Obat Antiretroviral dengan Kadar Viral Load pada Pasien HIV/AIDS dengan Koinfeksi Sifilis di RS H. Adam Malik Medan - Sukma, Triza Via; Br Tarigan, Elviyanti; Simbolon, Boyke Marthin; Br Ginting, Masita Unjuk; Sitompul, Christian Michael Oloan (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
The Human Immunodeficiency Virus (HIV) is a virus that targets and attacks the human immune system. Acquired immunodeficiency syndrome (AIDS) is an immunosuppressive condition (syndrome) closely associated with various opportunistic infections, secondary neoplasms, and certain neurological manifestations resulting from HIV infection. Adherence to antiretroviral therapy is a key factor in achieving optimal viral load suppression. Viral load testing is one indicator of the success of ARV treatment. The higher the viral load in the blood, the faster HIV disease progresses. Objective: To determine the relationship between adherence to antiretroviral medication and viral load levels in HIV/AIDS patients with syphilis co-infection at H. Adam Malik General Hospital. Methods: This study used an analytical observational research design with purposive sampling techniques, namely measuring antiretroviral medication adherence and viral load levels in HIV/AIDS patients with syphilis co-infection. Results: Of the 100 study subjects, the majority were male (82%) with the largest age group being 25-35 years (48%). The results of the analysis showed a highly significant relationship between the MMAS-8 compliance level and viral load status (χ² = 31.248; df = 2; p = 0.001). There was a clear pattern showing that the higher the level of adherence, the greater the proportion of patients who achieved viral suppression. Only 39% of patients achieved high adherence (score of 8), and there was a dramatic difference in viral suppression between low adherence (14.8%), moderate adherence (55.9%), and high adherence (76.9%).